Korelasi Learning Style Dengan Minat Belajar Pendidikan Agama Islam Pada Siswa - Fajrianti, Fajrianti; Suriyati, Suriyati; Jamaluddin, Jamaluddin; Rahmatullah, Rahmatullah; Nur, Makmur Jaya (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
Learning interest is one of the important factors in the success of learning, especially in Islamic Religious Education (PAI). One aspect that influences learning interest is students' learning style, which includes visual, auditory, and kinesthetic. This study aims to determine the correlation between learning style and students' interest in learning PAI. The research method used is quantitative with a correlational design. Data were collected through questionnaires given to students, then analyzed using the Pearson correlation statistical test. The results of the study showed that there was a significant relationship between learning style and interest in learning PAI. Students with learning styles that are in accordance with teaching methods tend to have higher learning interest compared to students who experience a mismatch in learning style and learning method. The implications of this study indicate that educators need to understand and adjust learning strategies to students' learning styles to improve their interest and learning outcomes in PAI subjects